The friend [videorecording (DVD)] - Nunez, Sigrid; Siegel, David (Director); McGehee, Scott; Murray, Bill, 1950 September 21-; Watts, Naomi, 1968-; Xhauflaire, Chloe (Decal, 2025)
A story of love, friendship, grief, and healing, about a writer who adopts a Great Dane that belonged to a deceased friend and mentor.